Cure characteristics and dielectric properties of magnetic composites containing strontium ferrite - Soloman, M. A.; Kurian, P.; Anantharaman, Maliemadom R.; Joy, Pattayil Alias (Journal of Elastomers and Plastics, 2005)
Hexagonal strontium ferrite (SrFe12O19) powders were synthesized by the conventional ceramic techniques. They were then characterized by the X-ray diffraction method and incorporated in the natural rubber matrix according to a specific recipe for various loadings of ferrite to produce rubber ferrite composites (RFCs). The processability of these compounds was determined by evaluating the cure characteristics namely, scorch time, cure time, minimum and maximum torque. The evaluation of the dielectric properties of ceramic strontium ferrite (SrF), natural rubber gum vulcanizate, and RFCs were done with the help of a Hewlett Packard (HP) impedance analyzer. The magnetic properties of these composites were studied using a Vibrating Sample Magnetometer (VSM). The effect of carbon black on the processability, and the magnetic and dielectric properties were also studied by the incorporation of carbon black into these composites. It has been found that the addition of these ferrites and carbon black does not affect the processability of these composites, whereas the physical properties are found to be modified. From the magnetic and dielectric measurements it has been found that flexible magnets having appropriate dielectric strength can be prepared by the incorporation of appropriate amount of SrF and carbon black in the natural rubber matrix.
Keywords: hexagonal ferrites; Magnetic materials; permanent magnets; rubber ferrite composites (RFCs); strontium ferrite

Colossal thermoelectric power in Gd-Sr manganites - Sagar, S.; Ganesan, V.; Joy, Pattayil Alias; Thomas, Senoy; Liebig, A.; Albrecht, M.; Anantharaman, Maliemadom R. (EPL, 2010)
Manganites belonging to the series Gd(1-x)Sr(x)MnO(3) (x=0.3, 0.4 and 0.5) were prepared by wet solid-state reaction and their thermoelectric power was evaluated. Thermoelectric power measurements revealed a peak value at similar to 40 K. All the samples exhibited a colossal thermopower at similar to 40K and in that Gd(0.5)Sr(0.5)MnO(3) exhibited a maximum value of similar to 35 V/K, which is the largest reported for these class of materials at this temperature. Temperature-dependent magnetisation measurements showed that the samples exhibit a phase transition from paramagnetic to spin-glass-like state at these temperatures. Plausible mechanisms responsible for the observed colossal thermoelectric power in Gd-Sr manganites are discussed. Copyright (C) EPLA, 2010

Contact potential induced enhancement of magnetization in polyaniline coated nanomagnetic iron oxides by plasma polymerization - Sethulakshmi, N.; Sooraj, V.; Sajeev, U. S.; Nair, Swapna S.; Narayanan, T. N.; Joy, Lija K.; Joy, Pattayil Alias; Ajayan, Pulickel M.; Anantharaman, Maliemadom R. (Applied Physics Letters, 2013)
The present work derives motivation from the so called surface/interfacial magnetism in core shell structures and commercial samples of Fe3O4 and gamma Fe2O3 with sizes ranging from 20 to 30 nm were coated with polyaniline using plasma polymerization and studied. The High Resolution Transmission Electron Microscopy images indicate a core shell structure after polyaniline coating and exhibited an increase in saturation magnetization by 2 emu/g. For confirmation, plasma polymerization was performed on maghemite nanoparticles which also exhibited an increase in saturation magnetization. This enhanced magnetization is rather surprising and the reason is found to be an interfacial phenomenon resulting from a contact potential. (C) 2013 AIP Publishing LLC.